Geographical distribution model of the fish Coryphaena hippurus (Perciformes: Coryphaenidae) according to climate change in the Pacific Oriental Tropical - Isaza-Toro, Estefania; Selvaraj, John Josephraj; Giraldo, Alan (Revista de Biología Tropical, 2024)
Introduction: Coryphaena hippurus is a species of commercial interest with a high migratory capacity, a characteristic that places it in tropical and subtropical environments, preferring areas with a temperature range between 21 and 30 °C and salinity close to 31 ppt. Although the population trend of C. hippurus is stable, the fishing of this resource is increasing and occupies important positions in the economy of the Eastern Tropical Pacific coastal countries, which demonstrates the need to design and strengthen conservation strategies for the adequate use of this resource. Given its location in tropical and subtropical environments, its availability and distribution could be affected by climate change. Objective: To analyze the current and future potential distribution of C. hippurus under climate change scenarios. Methods: Ten algorithms were used to model the potential distribution and current habitat suitability index of C. hippurus as a function of sea surface temperature, current salinity and velocity, and these results were then projected under the most extreme climate change scenario. Results: There were good performances with all the algorithms used, but the model generated with BIOCLIM (AUC: 0.89) was chosen because it also solves the problem of spatial and temporal bias found in the records of the species. The region of greatest habitat suitability for C. hippurus matches the oceanic fronts of the Eastern Tropical Pacific. Under future conditions of extreme climate change, the species distribution pattern indicates a contraction, relocation, and expansion of habitat south of the equator. Conclusions: Under conditions of extreme climate change, the distribution model for C. hippurus suggests a process of topicalization of marine ecosystems in the Eastern Tropical Pacific by 2100.